2004
DOI: 10.1007/s00264-003-0511-4
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood loss after cementless total hip arthroplasty?prospective randomized study in 40 cases

Abstract: We investigated the effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 20 publications
2
59
1
7
Order By: Relevance
“…Although earlier studies have shown similar results, they have included patients with different diagnoses and the dosage and timing of medication have been different. There has been only one study on uncemented hip arthroplasty with similar results (Yamasaki et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Although earlier studies have shown similar results, they have included patients with different diagnoses and the dosage and timing of medication have been different. There has been only one study on uncemented hip arthroplasty with similar results (Yamasaki et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Metaanalysis 2 confirms efficacy in decreasing perioperative blood loss and transfusion requirements in arthroplasty, although it seems to behave differently at the hip than the knee. In total hip replacement, several studies [3][4][5][6] show no decrease in intraoperative blood loss, but decreased postoperative blood loss and decreased transfusion requirements are generally confirmed, although 1 study showed no benefit. 7 In total knee replacement, the literature is more extensive and consistent in confirming that even operative bleeding is consistently decreased.…”
mentioning
confidence: 88%
“…De los 16 estudios, ninguno fue triple ciego, 14 fueron doble enmascarado 16---27,30,31 , uno era enmascarado solo para los pacientes 28 , y en otro, el cegamiento fue incierto 29 (tabla 2). Tres estudios 28,29,31 utilizaron estrategias informáticas para realizar la asignación aleatoria, y otros 3 utilizaron sobres cerrados para el ocultamiento de la asignación 23,28,29 . En un estudio la asignación al azar fue realizada por una persona/farmacéutico/residente que no participó en el estudio o en el cuidado de los pacientes 26 (tabla 2).…”
Section: Resultsunclassified